Ausspracheübungen für deutsche Polnischlernende – eine Lehrwerkanalyse - Anne-Marie Otto (Linguistische Treffen in Wrocław, 2021)
Standardized pronunciation is of great importance for foreign language acquisition. Phonetic skills are necessary for developing reading, writing, speaking and listening skills as well as for the entire language acquisition. Also, major pronunciation deviations can cause disruptions in communication. Therefore, it is important that pronunciation teaching and training is well integrated into foreign language teaching. Phonetic exercises in the textbooks are fundamental for this. Despite the fact that in recent years there has been an improvement of phonetic exercises in the teaching materials, still too little attention is paid to phonetics in the classroom. Using the method of teaching material analysis, the following article analyzes the phonetic practice material in three selected textbooks (+ workbooks and extra material) for Polish as a foreign language: „Hurra!!! Po Polsku“, „Polski, krok po kroku“ und „Witaj Polsko!”. German is assumed to be the learners’ source language. The results of a teaching material analysis can be used to make recommendations for teachers, e.g. which textbooks are recommendable concerning phonetic exercises or give advice how to work effectively with the given material. Among others it is important to fully exploit the potential of the phonetic exercises, to extend exercises if necessary, or to create one’s own additional material if the textbook used in class does not provide sufficient material. Using teaching material analysis, the three textbooks will be compared with each other regarding quantity, quality and selection of the phenomena. The single exercises will be classified using an exercise typology. The results of the analysis and the final comparison show that the phonetic exercise material still can be improved regarding quantity and quality. Overall, “Hurra!!! Po Polsku” already has many well-made pronunciation exercises. The phonetic exercises are well integrated and perform better in most points compared to the other two analyzed textbooks (+ workbooks and extra material).